Role of Topiramete in Moderate to Severe Perinatal Asphyxia - A Randomized Controlled Clinical Trial (Dhaka Shishu (Children) Hospital Journal, 2020)
Background: Topiramate is an anticonvulsant drugs that has multiple mode of mechanism of action. Topiramate appears to be effective as both an anti-seizure and neuroprotective agent in animal models of newborn brain injury.Objectives: To determine the neurological outcome of oral topiramate with moderate to severe hypoxic ischemic encephalopathy. Methods: This one year randomized controlled trial was carried out in the Neonatal ward and ICU of a tertiary care specialized hospital. A total of 64 neonate were enrolled in this study and were randomly assigned intervention group (Group-A, n=32) and control group (Group B=32). In case group oral topiramate 10mg/kg was given for 3 consecutive days along with standard treatment protocol. And control was given only standard protocol. Finally outcomes are compared.Results: Baseline clinical characteristics, age, sex, mode of delivery, arterial pH, residence, basic status of HIE cases were matched in both groups. This study has shown significant reduction of neurological impairment in all domain (gross motor, fine motor, vision hearing, speech) at 1 and 3 months in case than control. There is also early seizure control, early initiation of feeding, short duration of hospital stay in case (treatment) than control without any side effects.Conclusion: Early administration of topiramate to infants with moderate and severe HIE in perinatal asphyxia was very effective in controlling seizures, improving USG findings, and producing favorable neurodevelopmental outcomes at1 and 3 months of age.DS (Child) H J 2019; 35(2) : 135-140